2009
DOI: 10.1021/bi802246s
|View full text |Cite
|
Sign up to set email alerts
|

The Archetype γ-Class Carbonic Anhydrase (Cam) Contains Iron When Synthesized in Vivo

Abstract: A recombinant protein overproduction system was developed in Methanosarcina acetivorans to facilitate biochemical characterization of oxygen-sensitive metalloenzymes from strictly anaerobic species in the Archaea domain. The system was used to overproduce the archetype of the independently evolved gamma-class carbonic anhydrase. The overproduced enzyme was oxygen sensitive and had full incorporation of iron instead of zinc observed when overproduced in Escherichia coli. This, the first report of in vivo iron i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 16 publications
2
56
0
Order By: Relevance
“…We found that iron is the more catalytically active metal for Mt-CamH, and this enzyme is only the second CA shown to utilize this metal for catalysis. Mt-Cam contains Fe 2ϩ in the active site when it is overproduced in the closely related species M. acetivorans (18), a result that establishes that iron is the physiologically relevant metal in Mt-Cam and also supports the hypothesis that iron is the physiologically relevant metal in Mt-CamH.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We found that iron is the more catalytically active metal for Mt-CamH, and this enzyme is only the second CA shown to utilize this metal for catalysis. Mt-Cam contains Fe 2ϩ in the active site when it is overproduced in the closely related species M. acetivorans (18), a result that establishes that iron is the physiologically relevant metal in Mt-Cam and also supports the hypothesis that iron is the physiologically relevant metal in Mt-CamH.…”
Section: Discussionsupporting
confidence: 62%
“…Mt-Cam overproduced in Escherichia coli and purified aerobically contains zinc in the active site (2). However, overproduction in the closely related species Methanosarcina acetivorans yields an enzyme with 3-fold-greater CA activity and iron in the active site, establishing iron as the physiologically relevant metal (18).…”
mentioning
confidence: 99%
“…Because it is highly unlikely that CO can bind directly to the implicated amino acid residues (His 365 , His 394 , and Asp 367 ) in the RCK1 domain in a metal-independent manner, one possibility is that the His and Asp residues in RCK1 ligate a lowvalent metal ion, e.g. (52). Thus, further studies are required to clarify the relationship between CO and the potential metal binding sites in the RCK1 domain.…”
Section: Discussionmentioning
confidence: 99%
“…The different results obtained in aerobic and anaerobic conditions is explained by the fact that in aerobic conditions Fe 3+ is oxidized and rapidly loss from CAM enzyme, substituted by Zn 2+ contaminating buffers not treated with chelating agents. These results indicate Fe 2+ as the physiologically relevant metal [MacAuley et al, 2009;Tripp et al, 2004] in the active site for CAM enzyme. Interestingly, evidence for the role of ferrous ion in CA has been obtained also for the class.…”
Section: Heavy Metals As Carbonic Anhydrase Cofactorsmentioning
confidence: 62%